Electrochemical Deposition of MgO@ZnO Shell−Core Nanorod Arrays Largely Enhances the Photoelectrochemical Water Splitting Performance. Issue 8 (17th May 2017) - Wang, Hongwei; Tian, Jing; Li, Weibing
Abstract: Well aligned ZnO nanorod array (NRA) core coated with MgO nanolayer shell was fabricated via a facile pulse electrodeposition method. Using this method, a homogeneous MgO nanolayer could be formed on the surface of the wurtzite ZnO nanorod. This novel nanostructure with controllable shell thickness, provided a high photoinduced current density of 2.4 mA cm −2 at 1 V (vs. Ag/AgCl) under 100 mW cm −2 illumination (AM 1.5), which value is almost three times larger than that of pristine ZnO NRA and also much superior to those of analogous ZnO based photoanodes. The as‐prepared photoanodes exhibited excellent behaviors in photoelectrochemical (PEC) water splitting, significantly improved the photoconversion efficiency. This is attributed to the interface effect and surface hydrophilia provided by the MgO ultrathin nanolayer, suppressing the recombination rate of electron‐hole pairs and improving interfacial charge exchange capacity. Thus, this work provides a cost‐effective route to improve the performance of ZnO based photoanodes, in addition it can be used in other solar energy conversion devices, for example, this hydroxyl groups dominant surface can be employed for other visible light response semiconductors (CdS, CdTe etc.) assembly. Abstract : Time to split : The development of a simple and effective method to fabricate a well‐defined passivation layer on photoelectrodes is very necessary, owing to its importance for improving photoelectrochemical water splitting performance. Herein, a controllable electrochemical multipotential pulse deposition method is developed to deposit a MgO nanoshell on ZnO nanorod arrays, achieving a record photocurrent density (2.4 mA cm −2 ) for ZnO photoanodes.